Uwarunkowania i perspektywy dyskusji na temat narodu Śląskiego - Trosiak, Cezary (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The wave of transformations commenced by the ‘round table’ led the issue of the Silesian nation to be discussed by sociologists, political scientists, ethnologists, and – what is more significant – politicians. This issue was far from surprising for the researchers into the problems of Silesia as the native population of (both Upper and Lower) Silesia have clearly distanced themselves from a unanimous declaration of nationality, whether Polish or German, since the early 1980s. It was a semi-solution, adopted particularly by the Silesian living in Poland, to point to their Silesian nationality, as an alternative to being defined as a native Polish population.